Protection of the Worker from Hazards and Diseases in the Saudi Labor Law - Yusra Jaber Al-Dhubyani (International Journal of Law Research and Studies, 2025)
The study aims to assess the effectiveness of current laws in protecting workers from occupational hazards and diseases under the Saudi Labor Law. It reviewed the legal obligations placed on employers to protect workers’ health and their rights to compensation for occupational injuries and diseases. The study also discussed the legal mechanisms for ensuring compensation for workers affected by occupational hazards.The study concluded with several key findings, including that the Labor Law and the Social Insurance System have established a set of legal obligations for employers to ensure a safe working environment that protects workers from occupational hazards and diseases. The study also highlighted a significant legal challenge, namely the difficulty of proving the causal relationship between the disease and the work, particularly in cases where the disease is not included in the official list of occupational diseases, which places the burden of proof on the worker and weakens their chances of obtaining the deserved compensation. This reveals the urgent need to expand the recognition of occupational diseases.The study also provided several recommendations, the most important of which is the necessity of incorporating occupational risk assessments into the licensing requirements for factories and establishments, ensuring that no license is granted without submitting a comprehensive occupational health and safety plan. Additionally, the study recommends that the General Organization for Social Insurance periodically update the list of occupational diseases, as workers may contract an occupational disease not included in the official list, thus potentially not being entitled to compensation.
Keywords: Occupational hazards; occupational diseases; worker protection; Saudi Labor Law; occupational health and safety; Social Insurance System